1995
DOI: 10.1016/0014-5793(95)01339-3
|View full text |Cite
|
Sign up to set email alerts
|

Arginine‐427 in the Na+/glucose cotransporter (SGLT1) is involved in trafficking to the plasma membrane

Abstract: To investigate the role of charged intramembrane residues in the function of the rabbit Na+lglucose cotransporter (rbSGLT1) we substituted arginine-427 (R427) by alanine in the putative domain M9 SGLT1. This residue is conserved in all the members of the SGLT1 family. The mutant protein (R427A) was expressed in Xenopus oocytes and, although Western blot analysis revealed that it was produced in amounts comparable to wildtype, no function was measured. Freeze-fracture analysis showed that R427A SGLT1 was not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 11 publications
0
33
0
Order By: Relevance
“…Because the inhibition occurs via decrease in V max and is observed within hours, this type of regulation might theoretically be achieved by a decrease in the number of active molecules at the membrane due to endocytic retrieval from and/or exocytic insertion into the plasma membrane and/or rapid degradation by changes in the turnover number of individual exchanger molecules. Multiple plasma membrane transport proteins (7,16,29,37,48) were also shown to be regulated, at least in part, by cellular redistribution (endocytic retrieval from and/or exocytic insertion into the plasma membrane). PKC was reported to generally stimulate apical but not basolateral endocytosis in Caco-2 cells (18).…”
Section: /Ohmentioning
confidence: 99%
“…Because the inhibition occurs via decrease in V max and is observed within hours, this type of regulation might theoretically be achieved by a decrease in the number of active molecules at the membrane due to endocytic retrieval from and/or exocytic insertion into the plasma membrane and/or rapid degradation by changes in the turnover number of individual exchanger molecules. Multiple plasma membrane transport proteins (7,16,29,37,48) were also shown to be regulated, at least in part, by cellular redistribution (endocytic retrieval from and/or exocytic insertion into the plasma membrane). PKC was reported to generally stimulate apical but not basolateral endocytosis in Caco-2 cells (18).…”
Section: /Ohmentioning
confidence: 99%
“…Often, di-leucine endocytic signals occur close to arginine-based signals (Kalandadze et al, 2004). A previous study indicates that arginine-427 plays a critical role in the trafficking of the sodium-dependent glucose cotransporter (SGLT1) to the plasma membrane (Lostao et al, 1995), suggesting that the charged residue is essential in membrane protein trafficking. The disruption of R206 by the genetic variant cysteine and other substitutions might interfere with the conversed arginine-based motif (-LLFRLL-) (Fig.…”
Section: Oct1 Genetic Variants Metformin Asian Population 49mentioning
confidence: 99%
“…A number of studies have combined site-directed mutagenesis with the oocyte expression system to identify residues that contribute to the functioning of SGLT1 and its proper trafficking to the plasma membrane (6,7). A set of glycosylation mutants has yielded information on topology, and a chimera of the high affinity and low affinity isoforms has suggested that sugar binding is determined by the C-terminal half of the protein (8).…”
mentioning
confidence: 99%